Malaysian timbers- Rubberwood - Malaysia (Timber Trade Leaflet No.58)
Rubberwood is the timber of Hevea brasiliensis, or rubber trees as they are known locally. With an average air-dry density of 640 kg/m3, Rubberwood is classified as a Light Hardwood. The wood is whitish yellow or pale cream when freshly cut, and seasons to a light straw or light brown in colour. The texture of the timber ranges from moderately coarse to coarse, with grain ranging from straight to shallowly interlocking. The timber is easy to saw and machine. Rubberwood seasons fairly slowly with seasoning defects. Shrinkage from green to air-dry is low. Although the timber in its natural form is generally non-durable, this durability can be enhanced as it is very amenable to preservatice treatment. It is suitable for various uses such as semi-knock-down and complete-knock-down furniture, mouldings, kitchen wares, decorative and utility household items, glue-laminated products such as stairs, balusters, railings, steps, parquet and strip floorings, panellings, particle-boards, wood-cement-boards and moulded particle-boards for furniture components.
Keywords: Malaysia; Rubberwood